G277(P) Implementation of a Peer-Led Practice OSCE examination for Paediatric Medical Students at a busy Major Acute Trust. (7th April 2014) - Mitting, RB; Malley, M; Sohi, DK
Abstract : Aims: Peer-graded practice examinations can help medical students to achieve higher results in their final exams (1), and peer-led exam revision courses have demonstrated high levels of satisfaction (2, 3). Surveys show that the majority of medical students find exam practice provided by recent graduates as useful as consultant teaching (3). Our aim is to present our experience, over a 2 year period, of designing and implementing a practice Objective Structured Skills Examination (OSCE) in paediatrics, run by junior doctors from foundation year one to ST4 level, collating feedback from students and making improvements. Methods: 6 medical students have their paediatric placement every 4 weeks. During the 4th week, 5 members of staff run a 90-minute OSCE, consisting of 8 examined stations. 2 history-taking, 2 clinical skills, 2 counselling and 2 data-interpretation stations were designed, reflecting real life clinical situations as well as common exam scenarios. Stations were followed by 90 seconds of immediate individual verbal feedback by examiners who also took up roles of the actors in their scenarios. The OSCE was designed as 2 consecutive cycles of stations and ended with a group question and answer session and feedback forms. Results: We have collated written feedback from each student since September, 2012. The majority of students reported finding the OSCE useful exam preparation and something that they would recommend. We then asked the students to complete a further feedback questionnaire 1 year later, once they had completed their paediatric OSCE examination and 100% of respondents replied that the practice examination had been useful preparation for their final exams. Conclusion: We can show high levels of satisfaction from participants. The detailed feedback process enabled us to improve the exam, creating a useful revision aid, and an invaluable teaching tool. This process has been easy to implement, using junior doctors available from the rota in an extremely busy Major Acute Trust, without consultant supervision. It has been maintained despite the frequent turnover of junior doctors. We hope to use this model as a template for similar hospitals. References: Freeman S, Parks JW. How Accurate is Peer Grading? CBE Life Sci Educ . 2010 Winter;9(4):482–8. Alcamo AM, Davids AR, Way DP, Lynn DJ, Vandre DD. The Impact of a Peer-designed and –led USMLE Step 1 Review Course: Improvement in Preparation and Scores. Acad Med. 2010 Oct; 85 (10 supp) S45–8. Rashid MS, Sobowale, O, Gore D. A Near-Peer teaching programme, designed, developed and delivered exclusively by recent medical graduates for final year medical students sitting the final OSCE. BMJ Med Educ . 2011 Mar 17;11:11.